Explaining performance in health care: How and when top management competencies make the difference. Issue 4 (October 2019) - Vainieri, Milena; Ferrè, Francesca; Giacomelli, Giorgio; Nuti, Sabina
Abstract : Background: One of the most distinctive management competencies is related to the ability to structure the strategic vision, develop long-term plans, and communicate them efficiently to the employees in order to empower them to enact. These managerial competencies in complex organizations are strongly related to the capacity to engage professionals as a predictor of high-performing organizations. Purpose: The aim of this study was to investigate the relationship between top management competencies, information sharing, and organizational performance in public health care system and to look at the management role in assuring information sharing on organizational strategies to achieve professionals' engagement. Methodology/Approach: This relationship is empirically tested using the longitudinal data of public health care organizations from the Tuscany Region (Italy). The top management competencies and information sharing are evaluated by the heads of the departments. While information sharing refers to the organizational level (e.g., to convey the objectives), managerial competencies refer to the individual level (e.g., to manage conflict). A random effect regression model is estimated using average responses by the health organization. Data come from the multidimensional performance evaluation system (2008 to 2014 years). Results: Findings show that managerial competencies are positively associated to organizational performance. Moreover, managerial competencies are strongly linked to the information sharing process developed into the organizations. In particular, managerial competencies play a significant role on whole performance, and results are mediated by the use of mature information sharing instruments such as benchmarking of performance results. Conclusion: Systematic information sharing process regarding performance results, goals, and organizational structure provided by top management seems an effective strategy to engage professionals. Control variables suggest that top management tenure and turnover do not have an effect, whereas bigger health care organizations seem to negatively influence this relation. Practice Implications: Information sharing is the basis for clinicians' engagement and adds value to organizational performance.